2006
DOI: 10.1021/ma052414o
|View full text |Cite
|
Sign up to set email alerts
|

Using the “Switchable” Quality of Liquid Crystal Solvents To Mediate Segregation between Coil and Liquid Crystalline Polymers

Abstract: The discontinuous change in solvent quality of a liquid crystal (LC) solvent, 5CB, at the nematicisotropic phase transition produces abrupt changes in the phase behavior of solutions of coil and LC polymers and in the self-assembly of coil-LC block copolymers. Nematic 5CB is strongly selective for a side-group liquid crystal polymer (SGLCP), and isotropic 5CB is a good solvent for both SGLCP and a random coil (polystyrene, PS). In nematic 5CB, unfavorable LC-PS interactions drive phase separation in SGLCP-PS-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…A unique feature of triblock copolymer gels in LC solvent is the discontinuous change in solvent quality coincident with the first-order LC phase transitions. 31 This phenomenon is responsible for the large increase in G9, as much as an order of magnitude, observed over a y1 uC decrease from T NI to T NI 21 uC in dilute (greater than 1 wt% and up to 5 wt%) triblock copolymer gels; the solubility of the PS endblocks is much greater in the isotropic phase than in the nematic. The transition from gel to sol takes place over an extremely small temperature range compared to bulk BCPs or physical gels of BCPs swollen with isotropic solvent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A unique feature of triblock copolymer gels in LC solvent is the discontinuous change in solvent quality coincident with the first-order LC phase transitions. 31 This phenomenon is responsible for the large increase in G9, as much as an order of magnitude, observed over a y1 uC decrease from T NI to T NI 21 uC in dilute (greater than 1 wt% and up to 5 wt%) triblock copolymer gels; the solubility of the PS endblocks is much greater in the isotropic phase than in the nematic. The transition from gel to sol takes place over an extremely small temperature range compared to bulk BCPs or physical gels of BCPs swollen with isotropic solvent.…”
Section: Discussionmentioning
confidence: 99%
“…Their ternary phase behavior revealed that the differing affinity of isotropic 5CB for the PS and SGLCP resulted in macroscopic separation into PS-rich and SGLCP-rich phases, even under conditions where each homopolymer would be miscible with isotropic 5CB. 31 The reduced solubility of PS upon addition of SGLCP gives insight into the behavior of the block copolymer gels: PS endblocks associate even in isotropic 5CB because the SGLCP midblock drives the PS endblock out of the SGLCP-5CB solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17). 142 The SCLCP segments are compatible with LC solvents in both the nematic and the isotropic phases, while the coil polymer PS is insoluble in nematic LC solvents because placing a random-coil polymer in an ordered solvent requires the polymer to adopt an anisotropic conformation and distorts the nematic director field. Therefore the BCPs self-assemble into micelles with PS-rich cores and SCLCP-rich coronas.…”
Section: Amphiphilic Rod-coil Bcps Based On Liquid Crystalline Polymersmentioning
confidence: 99%
“…Later on, Finkelmann et al have shown that the block copolymer segment containing the mesogenic moieties feature a selective solubility in the low molecular weight liquid crystals, whereas the isotropic block is not soluble in the LC solvent [13]. As a result, the flexible segments of an AB-diblock copolymer associate and form a micelle core that is surrounded by a corona of soluble liquid crystalline blocks [14][15][16].…”
Section: Introductionmentioning
confidence: 99%